Trends in violence in England and Wales 2010–2014. Issue 6 (29th December 2015) - Sivarajasingam, Vaseekaran; Page, Nicholas; Wells, John; Morgan, Peter; Matthews, Kent; Moore, Simon; Shepherd, Jonathan
Abstract : Background: The National Violence Surveillance Network (NVSN) of emergency departments (ED), minor injuries units and walk-in-centres in England and Wales has brought clarity to contradictory violence trends derived from crime survey and police data. Gender, age-specific and regional trends in violence-related injury in England and Wales since 2010 have not been studied. Methods: Data on violence-related injury were collected from a structured sample of 151 EDs in England and Wales. ED attendance date and age and gender of patients who reported injury in violence from 1 January 2010 to 31 December 2014 were identified from attendance codes, specified at the local level. Time series statistical methods were used to detect both regional and national trends. Results: In total, 247 016 (178 709 males: 72.3%) violence-related attendances were identified. Estimated annual injury rate across England and Wales was 4.4/1000 population (95% CI 3.9 to 4.9); males 6.5/1000 (95% CI 5.6 to 7.2) and females 2.4/1000 (95% CI 2.1 to 2.6). On average, overall attendances decreased by 13.8% per year over the 5 years (95% CI −14.8 to −12.1). Attendances decreased significantly for both genders and all age groups (0–10, 11–17, 18–30, 31–50, 51+ years); declines were greatest among children and adolescents. Significant decreases in violence-related injury were found in all but two regions. Violence peaked in May and July. Conclusions: From an ED perspective, violence in England and Wales decreased substantially between 2010 and 2014, especially among children and adolescents. Violence prevention efforts should focus on regions with the highest injury rates and during the period May–July.